Distinguish seabed objects utilizing different marine acoustic techniques - Amr Z. Hamouda; Mohamed A. Nassar; Suzan M. El-Gharabawy (Egyptian Journal of Petroleum)
The marine acoustic techniques are powerful tools to investigate and identify the seabed objects by applying different processing and interpretation steps. Two types of marine acoustic imaging techniques used in this study; Side Scan Sonar (SSS) that mapping seabed features and identifies the objects on it, and Sub-Bottom Profiling (SBP) that providing information about sediment thicknesses and stratigraphic structure. The integration between these two marine acoustic techniques, as well as, ground truth data obtained from an underwater camera, was used to distinguish seabed objects; coastal boulder accumulations that are documented along the western Mediterranean coast of Egypt. The study and analysis of the collected data demonstrated that: the combination between side scan sonar, chirp sub-bottom profiling systems, and ROV images can successfully distinguish different types of objects. Generally, objects observed from SSS are indicated in the SBP as weak backscatter curves. The case study results, from analysis of SBP with ROV image to the object detected by SSS utilized three objects making a shadow in SSS seabed: boulder, hard substrate, and seagrass. The integration of these techniques resulting specifies the location of the geo-hazards area.